Analisis Kesalahan Siswa Kelas VIII Dalam Menyelesaikan Soal Uraian Pokok Bahasan Kubus - Alfian Multi Amrullah; Tri Astuti Arigiyati (UNION: Jurnal Ilmiah Pendidikan Matematika, 2018)
The purpose of the research are to find out the percentage of concept error, prosedur error, computation error, and the most dominant error in resolving the problem description of cube discussion subject VII A grade students MTs Negeri Ngablak The object of this research is studentâ€™s mistake in resolving the problem description of the set discussion subject. The type of this research is qualitative descriptive research. Data collection technique uses test technique and interview technique. Test Instrument in this research have 5 description problem test. The result of research indicate descriptively that students of MTs Negeri Ngablak undertake the average of concept error 67,77%, the average of procedure error 51,96%, and the average of computation error 28,41% with low category. The most dominant mistake type in resolving the problem which is done by VII A students MTs Negeri Ngablak is concept error.Â